2021
DOI: 10.47153/jbmr21.852021
|View full text |Cite
|
Sign up to set email alerts
|

Literature Review of Pandemic covid 19 Effects on Employee Compensation

Abstract: This article aims to determine the development of research on compensation during the Covid 19 pandemic in Indonesia. The method used is a qualitative method by conducting a literature study or literature review. The application used for the literature study is google scholar with the keyword "Covid 19 pandemic compensation". The results of the survey found nine articles regarding compensation. The results of this article's analysis indicate that studies regarding payment during the Covid 19 pandemic are studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 1 publication
0
5
0
1
Order By: Relevance
“…According to Safuan and Kurnia (2021), COVID-19 caused a significant amount of havoc to the pay systems of various organizations. The subsequent study effort was based on an examination of the context, and significant findings have made it clear that the compensation system became unsustainable during the lockdown.…”
Section: Impact Of Employee Compensation On Firm's Performancementioning
confidence: 99%
“…According to Safuan and Kurnia (2021), COVID-19 caused a significant amount of havoc to the pay systems of various organizations. The subsequent study effort was based on an examination of the context, and significant findings have made it clear that the compensation system became unsustainable during the lockdown.…”
Section: Impact Of Employee Compensation On Firm's Performancementioning
confidence: 99%
“…Making use of technology to work from distance, to receive e-training from distance; and to be assessed from distance all this created an uncomfortable HRM environment for employees. These working condition were not satisfying [16] .…”
Section: More Technological Integration In Hrm Means More Employee Is...mentioning
confidence: 92%
“…It encompasses monetary (base pay/bonuses) and non-monetary rewards (employee benefits) (Martocchio, 2017). It can influence employees' motivation, performance (Safuan and Kurnia, 2021;Sembiring et al, 2020), and retention (Elsafty and Ragheb, 2020). The study by Elsafty and Ragheb (2020) showed that financial benefits such as bonuses during COVID-19 are associated significantly with employees' retention.…”
Section: Curtailing and Compensationmentioning
confidence: 99%